Kuat Tekan Beton Menggunakan Material Tanah Mediteran Asal Dusun Kadinge - Abdias T Arrang; Parea Rusan Rangan; Salmon Sendana; Yulieanti S. Mapaliey (Jurnal Dynamic Saint, 2021)
Concrete is one of material that is widely used in infrastructure development, this is due to the abundance of concrete building materials available in nature. This study utilizes mediterranean soil as a substitute for fine aggregate and cement substitution to determine the feasibility of the mixed-concrete mediterranean soil against the achieved compressive strength. In this research, a laboratory experimental study method was used, that is conducting a compressive strength test on sample with the composition of the Mediterranean soil as a fine aggregate substitution of 25% and 50%, and the mediterranean soil passed sieve No. 200 which is heated to a temperature of 400 0 C as a cement substitute for 3% and 5%. The compressive strength of the concrete is 20 MPa with a slump of 100 mm. The results showed that the compressive strength of 25% and 50% fine aggregate substitution concrete was 20.05 MPa and 13.739 MPa, or only 94.23% and 60% compressive strength of concrete without mediterranean soil (21.235 MPa). Meanwhile, the compressive strength of 3% and 5% cement substitution concrete was 17.74 MPa and 14.53 MPa, or only 83.59% and 68.45% compressive strength of concrete without mediterranean soil.